O uso da meditação por doentes em cuidados paliativos para ajudar a lidar com a doença e fatores associados - Scoping Review. - Carolina Esteves Monnerat (2024)
ABSTRACT Introduction: Palliative care focuses on improving the quality of life for patients and families facing life-threatening and terminal diseases through the prevention and relief of suffering. In addition to conventional medical treatments, palliative care can also include a variety of non-pharmacological interventions to address the physical, emotional, and spiritual needs of patients. Meditation is a practice that can provide significant benefits for these patients, their families, and health professionals, offering a means to cope with pain, stress, anxiety, and other emotional difficulties that often accompany serious and progressive ailments. Objective: Evaluate and understand the effectiveness of meditation as a tool to help palliative care patients cope with illness and manage physical, emotional, social, and spiritual symptoms. Methods: Scoping review based on the principles advocated by the Joanna Briggs Institute. The databases consulted were PubMed, Scopus, and Web of Science in May 2024, using the keywords: "palliative care" AND "meditation", with a time frame defined from 2014 to 2024. Out of a total of 202 articles found, 10 articles were selected for the review. Results: Meditation can bring various benefits to patients in palliative care, promoting emotional and spiritual well-being and improving the quality of life for both patients and their caregivers. Incorporated into a holistic approach to palliative care, meditation can offer valuable support to patients and their families, helping them find peace and comfort during a critical period. Conclusions: There is preliminary evidence indicating that meditation offers a range of potential benefits for patients in palliative care, helping to promote emotional and spiritual well-being and improving the quality of life for both patients and their caregivers. As part of a holistic palliative care approach, meditation can provide valuable support for patients and their families, helping them find peace and comfort during a critical time in their lives. However, current research has encountered some limitations, such as small sample sizes, heterogeneity of studies, lack of standardization of meditation techniques, and inadequate follow-up durations. As a result, the overall quality of available evidence remains low, making it difficult to draw definitive conclusions about the effectiveness of this intervention in this population. Therefore, more research is needed, especially large-scale randomized clinical trials with rigorous methods, to confirm these initial findings and determine the impact of meditation practice on patients in palliative care.